Effects of a Whole-Body Electrostimulation Program on Strength, Sprinting, Jumping, and Kicking Capacity in Elite Soccer Players - Andre Filipovic, Marijke Grau, Heinz Kleinöder, Philipp Zimmer, Wildor Hollmann, Wilhelm Bloch (Journal of Sports Science and Medicine, 2016)
The aim of the present study was to investigate the effect of a 14-week dynamic Whole-Body Electrostimulation (WB-EMS) training program on muscular strength, soccer relevant sprint, jump and kicking velocity performance in elite soccer players during competitive season. Twenty-two field-players were assigned to 2 groups: WB-EMS group (EG, n = 12), jump-training group (TG, n = 10). The training programs were conducted twice a week concurrent to 6-7 soccer training sessions during the 2nd half of the season. Participants were tested before (baseline), during (wk-7) and after (wk-14). Blood serum samples for analyzing IGF-1 and CK were taken before each testing, 15-30min post and 24h post the training program. Our findings of the present study were that a 14-week in-season WB-EMS program significant increased one-leg maximal strength (1RM) at the leg press machine (1.99 vs. 1.66 kg/kg, p = 0.001), and improved linear sprinting (5m: 1.01 vs. 1.04s, p=0.039), sprinting with direction changes (3.07 vs. 3.25s, p = 0.024), and vertical jumping performance (SJ: 38.8 vs. 35.9cm p = 0.021) as well as kicking velocity (1step: 93.8 vs. 83.9 km·h-1, p < 0.001). The TG showed no changes in strength and performance. The EG revealed significantly increased CK levels 24h post training and yielded significantly higher CK levels compared to the TG. IGF-1 serum levels neither changed in the EG nor in the TG. The results give first hints that two sessions of a dynamic WB-EMS training in addition to 6-7 soccer sessions per week can be effective for significantly enhancing soccer relevant performance capacities in professional players during competitive season.